Pelatihan Produksi Konten Jurnalisme Warga pada Karang Taruna di Kenagarian Batipuah Baruah Kecamatan Batipuh Kabupaten Tanah Datar - AB Sarca Putera; Ike Sylvia; Nurlizawati Nurlizawati; Ayu Adriyani; Ikhwan Ikhwan (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
A dialogue with the community and the government of the Batipuah Baruah village was held to see the problems faced by the community today. In addition to ensuring that community service is participatory, this is also to ensure that the solutions offered are targeted. From this dialogue, found the problem on economic and socio-cultural sector. On economic sector, hidden unemployment with productive age is still found, while the use of online platforms in carrying out and developing economic activities by the Batipuah Baruah village youth is also still lacking. On socio-cultural issues, there are still non-optimal use of media (information and communication technology), in this case new media (websites, social media, and/or other online media). Utilization of information technology is a necessity today to answer these problems. Through situation analysis, the service program that is carried out is media content production training. Program implementation methods and approaches are training with pre-program, planning, production, and distribution, also post-program stages. Through this activity, it is possible to increase the ability of youth in Batipuah Baruah's Karang Taruna Nagari in planning, implementing and distributing content by producing 28 contents in the form of photos, videos and texts that are part of citizen journalism activities.